Seduction, advertising and postmodernity - Lipovetsky, Gilles (2008)
Contrary to what their critics hold, seduction, advertising and postmodernity are not indicative signs of a neoliberal conspiracy aiming at the expoliation of naive consumers. In this text the author shows that the above triad, even though despised by many, can have an emancipatory role.